‘Bacteroides ihuae’ sp. nov., a new bacterial species isolated from the human respiratory microbiome - Fonkou, M.D.M. (New Microbes New Infect, 2017)
We present the main features of ‘Bacteroides ihuae’ sp. nov., strain Marseille-P2824(T) (CSUR P2824), isolated from the sputum of healthy Frenchwoman living in Marseille.